THE EFFECT OF E-GOVERNMENT ON IMPROVING THE QUALITY OF POPULATION ADMINISTRATION SERVICES IN THE SERVICES POPULATION AND CIVIL REGISTRATION OF MEDAN CITY - H Silaban, Pantas; Nainggolan, Arlinton; Sinaga, Remina; Maria Gultom, Priska; Simamora, Hamonangan (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2022)
Based on the observations of researchers at the Department of Population and Civil Registration of Medan City, it was found that the implementation of e-government is still less attractive to some people in Medan City in managing and administering population documents. This problem is thought to be caused by the lack of knowledge and public participation in how to use the new system or e-government, so that people are less enthusiastic in carrying out online-based services or e-government. The object of research in this study is the effect of e-government on improving the quality of population administration services at the Department of Population and Civil Registration of Medan City.The research method used in this study is to use a systematic review to examine the unpreparedness of human resources (HR) for technological acceleration, while Pickering discusses the benefits of systematic reviews in research, especially for those who are completing a doctoral program. The research begins by setting search keywords, then searching data through a predetermined search engine application.The results of the research at the Medan City Population and Civil Registration Office found obstacles, namely the lack of public knowledge regarding how to use the e-government system in the service process, and the lack of community participation in using the e-government system at the Medan City Population and Civil Registration Service. Efforts need to be made to overcome these obstacles, namely by regularly communicating or socializing related to the procedures for using the e-government system and must convince the public that e-government can facilitate service activities. The conclusion that can be drawn.